(untitled) (Proceeding of SINERGY, 2026)
This research analyzes the influence of Strategic Management Accounting (SMA) Integration on ESG Performance at PT Perkebunan Nusantara III (Persero), with Organizational Capabilities as a moderating variable and Regulatory Pressure as a mediating variable. The paradigm shift from shareholder capitalism toward stakeholder capitalism requires companies to create sustainable value for all stakeholders. As the largest State-Owned Enterprise (BUMN) in the palm oil and rubber plantation sector, PTPN III faces multidimensional pressure to integrate ESG practices into its operational activities. This research employs a causal explanatory design using a questionnaire survey method with 33 respondents from executive, middle, and operational management levels. Data were analyzed using linear regression, path analysis, and Moderated Regression Analysis (MRA). The results demonstrate that SMA Integration has a statistically significant positive effect on ESG Performance (β=0.633; p<0.001). However, Organizational Capabilities do not moderate this relationship (p=0.090), and Regulatory Pressure does not mediate the relationship between SMA Integration and ESG Performance (p=0.106). The primary findings indicate that PTPN III has effectively utilized SMA information in achieving ESG performance targets without relying on regulatory pressure or organizational capabilities as mediating or moderating factors. This research contributes theoretically by integrating Institutional Theory and Resource-Based View in the context of sustainability, and provides practical contributions as a benchmark for ESG implementation in the Indonesian plantation sector.